Evaluation of Four Sampling Techniques for Surveillance of Culex quinquefasciatus (Diptera: Culicidae) and Other Mosquitoes in African Rice Agroecosystems. Issue 3 (28th October 2014) - Muturi, Ephantus J.; Mwangangi, Joseph; Shililu, Josephat; Muriu, Simon; Jacob, Benjamin; Mbogo, Charles M.; John, Githure; Novak, Robert
Abstract : Field studies were conducted in a rice, Oryza sativa L., agroecosystem in Mwea Kenya to compare the efficiency of CO2 -baited Centers for Disease Control (CDC) light traps against nonbaited CDC light traps and gravid traps against oviposition traps in outdoor collection of Culex quinquefasciatus Say (Diptera: Culicidae) and other mosquitoes. Collectively, 21 mosquito species from the genera Culex, Anopheles, Mansonia, Ficalbia, and Aedes were captured during the 10-wk study period. Cx. quinquefasciatus was the predominant species in all trap types with proportions ranging from 57% in the nonbaited CDC light traps to 95% in the gravid traps. Significantly higher numbers of Cx. quinquefasciatus and Culex annulioris Theobald were collected in the CO2 -baited CDC light traps than in the nonbaited CDC light traps, but the numbers of other mosquito species, including malaria vectors Anopheles arabiensis Patton and Anopheles funestus Giles did not differ significantly between the two trap types. More Cx. quinquefasciatus females were collected in grass infusion-baited gravid traps than egg rafts of this species in oviposition traps containing the same infusion. Although most mosquitoes captured in CO2 -baited and nonbaited CDC light traps were unfed, most of those collected in gravid traps were gravid. From these findings, it is concluded that at least in the rice-growing area of Mwea Kenya, CO2 -baited CDC light traps in conjunction with gravid traps can be used in monitoring of Cx. quinquefasciatus both for control and disease surveillance.